2014
DOI: 10.1007/s00268-014-2664-2
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Cohort Study of the Adoption of Elastic Stable Intramedullary Nailing for the Treatment of Pediatric Femur Fractures in Kumasi, Ghana

Abstract: The initial experience of operative treatment of femoral shaft fractures in children using ESIN was positive, with improved rates of treatment success and no surgical complications. Because of the high cost of implants, direct costs of treatment remained higher with ESIN despite reductions in length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…A multicenter study reported that an increasing number of surgeons performed FIN surgery in 3–5 years old children. FIN fixation costs more and requires reoperation to remove the internal fixation device [ 21 , 22 ]. In this study, the cost of FIN surgery was significantly higher than that of traction combined with spica braces ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study reported that an increasing number of surgeons performed FIN surgery in 3–5 years old children. FIN fixation costs more and requires reoperation to remove the internal fixation device [ 21 , 22 ]. In this study, the cost of FIN surgery was significantly higher than that of traction combined with spica braces ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%